Apreciación local y calidad de agua en dos comunidades rurales de la carretera Iquitos - Nauta, región Loreto - 2022 - Pezo Guibin, Marcelo (2022)
This research was carried out in the localities of Cahuide and Ex Petroleros, which are located on the Iquitos-Nauta highway, and where the drinking water project, initiated by the Ministry of Housing, Construction and Sanitation and local governments, is being developed. The objective was to determine the quality of water for drinking or human consumption, with physicochemical and bacteriological analysis reports, in addition to analyzing the local appreciation of the quality of water consumed by the two populations along the Iquitos-Nauta highway, in the year 2022. As a reference, we used the regulations authorized by MINSA (Ministry of Health) of the Regulation of Water Quality for Human Consumption, in which MINSA's Supreme Decree N°031-2010-SA is inserted. Samples were obtained at different points of pumping or intake of water to the treatment plant, obtaining results such as: The drinking water for the intake of the study populations, is not suitable for human consumption, because the concentration or quantification of bacteriological parameters such as total and fecal coliforms, prevail over the maximum permissible limit: 0 CFU/100mL. As for the physical parameters or measurements such as aluminum color, turbidity, pH, do not reach the maximum permissible limits. To report the quality of the water, the respondents said, 40%, that it satisfies their needs for consumption, it is potable and they encourage the consumption of this water to other people in the community.